2018
DOI: 10.1016/j.schres.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Substantia nigra ultrastructural pathology in schizophrenia

Abstract: Schizophrenia is a severe mental illness affecting approximately 1% of the population worldwide. Despite its prevalence, the cause remains unknown, and treatment is not effective in all patients. Dopamine is thought to play a role in schizophrenia pathology, yet the substantia nigra (SN), the origin of dopaminergic pathways, has not been studied extensively in schizophrenia. In this study, electron microscopy was used to examine neurons, oligodendrocytes, and myelinated axons in the SN of normal controls (NCs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 64 publications
0
10
0
2
Order By: Relevance
“…In another recent study (87) authors reported that a greater decrease of myelination in substantia nigra was observed in cases of schizophrenia with a poor response to treatment in comparison with responders and healthy controls. This finding does not allow to conclude that substantia nigra aberrations may be considered as predictors of treatment resistance.…”
Section: Resultsmentioning
confidence: 93%
“…In another recent study (87) authors reported that a greater decrease of myelination in substantia nigra was observed in cases of schizophrenia with a poor response to treatment in comparison with responders and healthy controls. This finding does not allow to conclude that substantia nigra aberrations may be considered as predictors of treatment resistance.…”
Section: Resultsmentioning
confidence: 93%
“…Notably, post-mortem analysis performed in the prefrontal cortex of schizophrenic patients revealed oligodendrocyte ultrastructural abnormalities [183]. Similarly, cytoskeletal derangements within nigro-striatal DA neurons and axons were recently evidenced in another cohort of schizophrenic brains [184]. Remarkably, a very recent neuropathological examination provided evidence for TDP-43-positive cytosolic inclusions and dystrophic neurites in the brain of a patient diagnosed with FTLD presenting brief psychotic episodes and catatonia, which is a syndrome related to schizophrenia [120].…”
Section: Cytoskeletal Abnormalities and Neuronal Inclusions In Schmentioning
confidence: 99%
“…Exposure of C57BL/6 mice to cuprizone results in demyelination and behaviors that resemble some of those seen in schizophrenia. Cuprizone is a copper chelating agent that when included in the rodent diet for weeks will result in mice developing widespread demyelination, oligodendrocyte loss and myelin breakdown which is similar to changes seen in post-mortem brains of individuals who had schizophrenia (Gudi et al, 2014 ; Walker et al, 2018 ). This model was used to test the effects of haloperidol, clozapine, quetiapine on WM recovery and remyelination (Xu et al, 2011 ).…”
Section: Pharmacological Wm Targets In Treatment Resistant Schizophrementioning
confidence: 93%
“…Six samples were from treatment resistant subjects and 6 samples were from treatment responsive individuals (a further 2 samples were unknown for treatment response) and these were compared to 9 normal controls. Though this is a small sample size study, tissue from the substantia nigra of treatment resistant patients showed aberrant myelination characterized by increased G ratio (associated with decreased myelin thickness), axons without cytoplasm, and protrusions into the myelin sheath (Walker et al, 2018 ). The patients in both groups had an average duration of disease of 24 years so while treatment exposure is likely to have been different between groups, these results suggest cellular level changes that may be integral to treatment resistance.…”
Section: What Evidence Do We Have For Wm Changes In Schizophrenia Beimentioning
confidence: 99%